Histopathology liver of the Mus musculus based on the intensity of induction time of ciu alcoholic beverages - Magdalena Budi Verena Putri; Fitria Diniah Janah Sayekti (Institute of Advanced Engineering and Science, 2026)
The ciu alcoholic drink is a drink made from molasses that is fermented and undergoes a distillation process to obtain 25% ethanol that can cause liver’s damage. The purpose of this study was to determine the difference in the histopathological effect of the liver of Mus musculus treated with different periods. This study was experimental with 5 treatment groups, including negative control and 4 treatments of ciu, a traditional alcoholic drink by administering 0.6 ml/25 g for 3, 7, 14, and 30 days. The results of macroscopic observations showed that there was a difference between the control group and the ciu treatment, namely, the liver was brownish red when given the ciu alcoholic drink for 3 days and the liver organs were blackish red when given for 7 days, and on the liver weight, the longer the ciu traditional alcoholic drink is given, the greater the liver weight. The results of the significant value of the analysis of variance (ANOVA) test were 0.000, so it can be seen that the administration of the traditional alcoholic drink ciu can affect the histopathological of the mice liver, where the organ that is given ciu alcoholic beverages progressively causes tissue damage such as degeneration and necrosis.